Dense high-aspect ratio 3D carbon pillars on interdigitated microelectrode arrays. (November 2015) - Amato, Letizia; Heiskanen, Arto; Hansen, Rasmus; Gammelgaard, Lauge; Rindzevicius, Tomas; Tenje, Maria; Emnéus, Jenny; Keller, Stephan S.
Abstract: In this work we present high-aspect ratio carbon pillars (1.4 μm in diameter and ∼11 μm in height) on top of interdigitated electrode arrays to be used for electrochemical applications. For this purpose, different types of 2D and 3D pyrolysed carbon structures were fabricated and characterised including surface- and microstructure, electrical and electrochemical properties. A pre-treatment of oxidised Si wafers is introduced to eliminate electrode delamination and ensure structure stability in water during long time-experiments. Additionally, a heat treatment method is reported for regeneration of pyrolysed carbon films with increased film resistance due to oxidation during storage.